183k views
0 votes
18x -16y = -312
78x -16y = 408

User ChrisOram
by
5.2k points

1 Answer

1 vote

Answer:

(-12,6)

Explanation:

using elimination method multiply the second equation by -1

18x - 16y = -312

-78x + 16y = -408

add the two equations

60x = -720

divide by 60

x = -12

plug -12 into the first equation

18(-12) - 16y = -312

-216 - 16y = -312

-16y = -96

y = 6

User Niko Gamulin
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.